2017
DOI: 10.1051/matecconf/201712001008
|View full text |Cite
|
Sign up to set email alerts
|

Repair of reinforced concrete beams using carbon fiber reinforced polymer

Abstract: Abstract. This research paper is part of an ongoing research on the behaviour of Reinforced Concrete (RC) beams retrofitted with Externally Bonded Carbon Fiber Reinforced Polymer (EB-CFRP). A total of 5 largescale rectangular beams, previously damaged due to shear loading, were repaired and strengthened with EB-CFRP and tested in this study. The major cracks of the damaged beams were injected with epoxy and the beams were wrapped with 2 layers of EB-CFRP discrete strips with 100mm width and 150mm center to cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 16 publications
1
7
0
1
Order By: Relevance
“…This phenomenon has also been reported by others [4,6,10]. However, debond of CFRP sheets from the strengthened beams due to high shear stress and occurrence of diagonal shear crack has been identified as the major problem for this strengthening system [10][11]. Bukhari et al [7] found that fiber orientation affects the ability of CFRP sheets to support shear forces.…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…This phenomenon has also been reported by others [4,6,10]. However, debond of CFRP sheets from the strengthened beams due to high shear stress and occurrence of diagonal shear crack has been identified as the major problem for this strengthening system [10][11]. Bukhari et al [7] found that fiber orientation affects the ability of CFRP sheets to support shear forces.…”
Section: Introductionsupporting
confidence: 60%
“…Research reports on the application of fiberreinforced polymers began to be published in 1971 [1] and a large number of studies have been reported in recent years due to the need for new materials to retrofit structures, high-performance FRP materials and rapid development of FRP technology in the chemical industry [3][4][5][6][7][8][9][10][11][12]. Khalifa et al [3] showed that strengthening using CFRP sheets increased the shear capacity of reinforced concrete beams.…”
Section: Introductionmentioning
confidence: 99%
“…O modelo mostrou uma maior precisão em comparação com os existentes na literatura. Karzad et al (2017Karzad et al ( , 2019 Foster et al (2016).…”
Section: Estudos Experimentais Usando Técnicas De Reforço Externa (Eb) E Nsm Ao Cisalhamento Com Prfunclassified
“…encounter numerous shortcomings, e.g. problematic and slow application, and lack of durability [4]. A retrofitted beam with CFRP laminates can resist up to 170 % of the maximum load as compared to control beams [5].…”
Section: Introductionmentioning
confidence: 99%